Adipose tissue-specific ablation of PGC-1β impairs thermogenesis in brown fat - Funda, Jiří; Villena, Josep A; Bardova, Kristina; Adamcova, Katerina; Irodenko, Illaria; Flachs, Pavel; Jedlickova, Ivana; Haasova, Eliska; Rossmeisl, Martin; Kopecky, Jan; Janovska, Petra (Disease models & mechanisms, 2022)
Impaired thermogenesis observed in mice with whole-body ablation of peroxisome proliferator-activated receptor-γ coactivator-1β (PGC-1β; officially known as PPARGC1B) may result from impaired brown fat (brown adipose tissue; BAT) function, but other mechanism(s) could be involved. Here, using adipose-specific PGC-1β knockout mice (PGC-1β-AT-KO mice) we aimed to learn whether specific PGC-1β ablation in adipocytes is sufficient to drive cold sensitivity. Indeed, we found that warm-adapted (30°C) mutant mice were relatively sensitive to acute cold exposure (6°C). When these mice were subjected to cold exposure for 7 days (7-day-CE), adrenergic stimulation of their metabolism was impaired, despite similar levels of thermogenic uncoupling protein 1 in BAT in PGC-1β-AT-KO and wild-type mice. Gene expression in BAT of mutant mice suggested a compensatory increase in lipid metabolism to counteract the thermogenic defect. Interestingly, a reduced number of contacts between mitochondria and lipid droplets associated with low levels of L-form of optic atrophy 1 was found in BAT of PGC-1β-AT-KO mice. These genotypic differences were observed in warm-adapted mutant mice, but they were partially masked by 7-day-CE. Collectively, our results suggest a role for PGC-1β in controlling BAT lipid metabolism and thermogenesis. This article has an associated First Person interview with the first author of the paper.
Keywords: PPARGC1A; Animals; RNA-Binding Proteins; proteiny vázající RNA; Humans; Peroxisome Proliferator-Activated Receptor Gamma Coactivator 1-alpha; lidé; Adipose Tissue, Brown; hnědá tuková tkáň; zvířata; Adipocytes; Mice; Thermogenesis; termogeneze; Transcription Factors; transkripční faktory; tukové buňky; myši